Model Pembelajaran Berbasis Project-Based Learning Digital untuk Meningkatkan Literasi Numerasi Siswa Sekolah Dasar - Asri Handayani; Melin Sasmita; Ahmad Paerus (PGSD UNU NTB, 2025)
This study aims to develop and test the effectiveness of a digital Project-Based Learning (PjBL) learning model in improving elementary school students' numeracy literacy. The background of this study is the low numeracy literacy skills due to the dominance of conventional learning and minimal technology integration. The method used was Research and Development, with stages of needs analysis, model design, tool development, expert validation, and implementation in fifth grade elementary schools. The results showed that the developed model had a high level of feasibility based on expert assessments of content, construction, and language aspects. The model's implementation increased student engagement through contextual and collaborative project activities. Students were able to understand numeracy concepts more deeply and apply them to real-life situations. Furthermore, there was a significant increase in numeracy literacy skills after the model's implementation. Students also demonstrated improvements in critical thinking and problem-solving. The integration of digital technology has been shown to support more interactive and effective learning. Thus, the digital PjBL model can be a relevant alternative learning strategy in the digital era.